Drugstores and Druggists - Valdizán, Hermilio (1920)
Little has been written about medicine among the early inhabitants of our Peru and off the excellent contribution made to this study by our teachers and LAVORERIA AVENDAÑO; by PATRON, MUÑIZ, LORENA, Tello, Olano and some other doctors, there is not enough to establish the true good characteristics overlaid Tahuantisuyo among the inhabitants of the exercise of medical science material. None of the authors have named has any that would ensure that the Indians of Peru primitive exercised Pharmacy or something that could preserve some semblance Pharmacy news. It is assumed that this lack of information is consistent with the lack of exercise of the profession in the early Peru. Presumably among the vassals of Manco, the doctor was at the same time and served apothecary both functions without a tendency to mark the professional division. Footprint this concentration of professions, in one individual, yet we find in purely indigenous healers in those healers that roam the streets and alleys of our great people, wearing their picturesquely hung colored ponchos and carrying arms depots yervas and medicinal products.